Mathematics Apps Under the Magnifying Glass – An Analysis of the Inventory of Math Apps for Primary Schools Using German-Language Apps as A Case Study - Walter, Daniel; Schwätzer, Ulrich (Technology, knowledge and learning, 2025)
The usage of digital media, especially tablet apps, is currently a major concern in educational settings. A controversial discussion is also taking place in relation to mathematics education at primary schools. While on the one hand there are empirical findings on helpful isolated examples and related subject-didactic potentials of digital media, on the other hand numerous apps are criticized. Systematic analyses of the app stores inventory are rare, however. This article therefore deals with the analysis of the app store’s inventory of mathematics apps available for primary school use. Using the German app market as an example, 227 apps were analyzed. The results show that those apps are mainly located in the content-related area of numbers and operations , while process-related competencies and subject-didactic potentials of digital media are largely neglected. Moreover, apps focus on unstructured forms of practising fluent calculation. All in all, only a fragment of mathematics learning at primary schools is addressed, with frequently no consideration of subject-didactic potentials in mathematics apps, making the need for development of subject-didactically based mathematics apps obvious.